Perceived affordances of a collaborative virtual teacher education course on CLIL and technologies during remote teaching - El Kadri, Michele Salles; Calvo, Luciana Cabrini Simões; Passoni, Taisa Pinetti; Dantas-Whitney, Maria (Revista X, 2023)
The objective of this paper is both to describe the course syllabus and the activities implemented in a course on CLIL and technologies for pre-service and in-service teachers from three public universities in Paraná, and also examine the perceived affordances of the initiative. The theoretical framework of affordances guided the analysis and results indicate that the interactions provided by the online course allowed teachers to learn about CLIL, have opportunities to practice their language skills, articulate the use of technological resources and also reflect about pedagogical issues specific to the English language. For the professors in charge of the initiative, it allowed them to collaborate through the course planning as well as through researching/learning together in an international online experience. The affordances for our institutions include the incorporation of new perspectives into their curriculum as well as the development of internationalization at home practices. The proposal also allowed some room for identifying some limitations such as lack of time, no interactions among peers from different regions; no involvement with proposed ethnographic case study activities, aspects which impaired community building.